Kajian Regulasi Hukum Pidana Dalam Menangani Kejahatan Teknologi Informasi - -, Sugiaryo - (serambi hukum, 2010)
Abstract The development of information technology, besides having positive impact, it also has negative ones. The positive impact is the trend on technological development with all human creativity forms and the negative one is the emerging crime modus in Cyber world. The existing instruments of positive crime code (KUHP) still has difficulties in handle the development of IT crime , especially in relation with system or evidential means ( article 184 KUHAP verse 1 character c which still has not been acknowledging computer data as the evident due to digital in nature). Additionally, there are several articles which are inappropriate to be implemented in IT crime, that is fine which are very light ( can be replaced with jail ) in IT crimes which can result in huge financial loss, even it can paralyze networking system. The emerging of the acts No. 11/2008 on electronicÂ  information and transaction is expected to be able in providing secured, fair feeling and law authorization for the user and provider of informational technology and also able to overcome information technology crimes. Keywords: Regulation policy, crime code, information technology crimes .